First Annual Short Course in Educational Leadership : Littledale Conference Centre, St. John's, Newfoundland, February 22-27,1987. Day 2. Plenary session. Tape 1 of 2. - Memorial University of Newfoundland. School of Continuing Studies and Extension; Memorial University of Newfoundland. Division of Educational Technology (Memorial University of Newfoundland. School of Continuing Studies and Extension; Memorial University of Newfoundland. Division of Educational Technology, 1987)
Dr. Vernon Snelgrove describes the results of his survey about collective bargaining as it relates to teachers in Newfoundland and Labrador and the impact of collective bargaining. ends mid sentence